Culture education-based model for the modern organisation - Walaszczyk, Ludmiła (Journal of Education Culture and Society, 2021)
Aim. The aim of the research is to support the organisation’s management through raising awareness on cultural diversity in the multicultural environment, and presenting a complex model covering the cultural issues in the multicultural organisation. Methods. The model has been developed based on the research carried out between 2018 and 2021 in the Cultural Risk in the Organisation in the Globalisation Era – Competences vs. Reality project. The author used literature review and a survey questionnaire as research methods. To develop the model for staff management at a multicultural organisation, a survey questionnaire directed to 154 staff members of multicultural organisations in five countries (Poland, Italy, Latvia, Cyprus, and the UK) was used. Results. As a result of the analysis, the following key areas have been identified: cross-cultural awareness, understanding different cultures, stereotypes, communication, teamwork, leadership and hierarchy, learning styles, and qualities in the workplace. The improvement of the staff in the aforementioned areas makes them more aware of the cultural diversity in organisations and of different cultural risks that may occur. Conclusions. There is a strong need for a continued consideration and improvement of the awareness regarding cultural diversity, as it is an element of modern and changing economy which may influence the continuity of every organisation. Cognitive value. Key topics related to competences for mitigating cultural risks were identified. They were used as elements of the complex model which can be used at a multicultural organisation in the process of training the staff in the area of cultural diversity.